2022
DOI: 10.1177/09544062221075987
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the incremental sheet forming process and process parameters on aluminum sheets based on the vertical step sizes

Abstract: The Incremental Sheet Forming (ISF) is an effective forming method developed especially for rapid prototyping and small-batch production of sheet metals. The selection of parameters (in particular, vertical step size and toolpath geometry) in ISF is crucial. Besides, each parameter has different effects on the desired geometry, sheet thickness, forming time, and productivity. In this study, the ISF process was analyzed by investigating the effects of ISF parameters. For this purpose, AA5754 sheets were formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…Results showed that a decrease in vertical step size and an increase in feed rate resulted in a considerable reduction in surface roughness. Malyer and Sonmez 19 studied the effect of selected parameters on the response such as forming time, geometric tolerance, and sheet thickness while incrementally forming AA5754 sheets. According to the Pareto analysis, spindle speed and feed rate are the two parameters that significantly affect toolpath strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that a decrease in vertical step size and an increase in feed rate resulted in a considerable reduction in surface roughness. Malyer and Sonmez 19 studied the effect of selected parameters on the response such as forming time, geometric tolerance, and sheet thickness while incrementally forming AA5754 sheets. According to the Pareto analysis, spindle speed and feed rate are the two parameters that significantly affect toolpath strategies.…”
Section: Introductionmentioning
confidence: 99%